Die Selous-Game Reserve/Tanzania - Naturschutz, Jagdtourismus und nachhaltige Entwicklung in Afrikas größtem Wildreservat - Vorlaufer, Karl (ERDKUNDE, 1998)
Wildlife is an important resource in many African countries. This is shown by the importance of safari and hunting tourism for many regions, but also by the use of game by the native population as a source of meat. During colonialism, however, large areas of conservation were identified without considering the traditional claims of the local population. Now, as a result of population growth, land-use conflicts between population, conservation and tourism have become aggravating. Especially poaching threatens the wildlife’s survival. This study uses the hypothesis that a regulated hunting tourism within the confines of a comprehensive wildlife management could be an instrument for sustainable development of wildlife as a resource, but only if the native population becomes more involved in the proceedings of hunting tourism and in the planning and implementation of nature conservation. The Selous G.R. is used as an example to show attempts, successes and problems of the population’s participation in conservation and of the economic and ecological importance of hunting tourism. Considering the very low agricultural potential of the Selous G.R. (poor soils, tsetse-fly) and orientated towards the aim to preserve the reserve’s high biodiversity hunting tourism proves to be the ideal land use in the economic interests of the population. In the long-term, however, benefits from tourism will not compensate for opportunity costs which result from the closing of the reserve for other purposes. Tanzania will need massive financial support from wealthier nations in order to assure the lasting preservation of the Selous G.R. as a World Natural Heritage Site of the UNESCO.